2010
DOI: 10.1016/s1734-1140(10)70328-5
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenol C60(OH)24 prevents doxorubicin-induced acute cardiotoxicity in rats

Abstract: Results obtained in vitro suggested that fullerenol's antiproliferative properties and protective effects against doxorubicin (DOX) cytotoxicity are mediated by antioxidative and hydroxyl radical scavenger activity. The aim of this study was to examine the influence of fullerenol on acute cardiotoxicity after the administration of a single high dose of DOX in vivo. The experiment was performed on male Wistar rats randomly divided into five groups, each containing eight individuals, that were treated as follows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 24 publications
3
33
0
8
Order By: Relevance
“…Among numerous reported fullerene derivatives, nanofullerol is the most extensively studied, and has been implicated as a powerful antioxidant in the biomedical field. [48][49][50][51][52][53][54][55][56] Therefore, fullerol was selected in our present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among numerous reported fullerene derivatives, nanofullerol is the most extensively studied, and has been implicated as a powerful antioxidant in the biomedical field. [48][49][50][51][52][53][54][55][56] Therefore, fullerol was selected in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with those previously reported that nanofullerol provided protection against cell death induced by ROS in a variety of cells and tissues, including keratinocytes 62 and endothelial, 63 heart, liver, kidney, testes, and lung tissues. 50,51,64,65 It is well known that GAGs are the dominant part of the proteoglycan aggrecan, and aggrecan is a major component of the extracellular matrix in both chondrocytes and NP cells. 66,67 Yudoh et al reported that a water-soluble fullerene prevents matrix degradation in human chondrocytes under catabolic stress induced by H 2 O 2 and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…31 Our present data showed that fullerol served as an antioxidant in human ADSCs without cytotoxicity at doses up to 10 µM (Figures 1 and 2), and this is in agreement with a majority of previous reports with regards to other tissues and cell types. [17][18][19]28,[32][33][34][35][36][37][38][39] It has been shown that ROS inhibit osteogenesis and bone formation. Mody et al 40 reported that three oxidants, hydrogen peroxide (H 2 O 2 ), xanthine, and xanthine oxidase, and minimally oxidized low-density lipoproteins inhibited osteoblastic differentiation of MC3T3-E1 mouse bone preosteoblast cell line and M2-10B4 mouse marrow stromal cell line, while increasing intracellular oxidative stress.…”
mentioning
confidence: 99%
“…Lactate dehydrogenase (LDH) and α-hydroxybutyrate dehydrogenase (α-HBDH) in cardiomyocytes were marks to evaluate the tissue injuries. Both of them being elevated by DOX decreased by C60(OH)24 [35]. Except the cardioprotection, C60(OH)24 prevented the oxidative injury from the lung and kidney as well.…”
Section: Radical Scavenger: Prevent Oxidative Damage From Dox and Ccl4mentioning
confidence: 94%
“…In addition, 100 mg/kg C60(OH)24 maintained the level of antioxidative enzymes superoxide in cardiomyocytes which would be enhanced by 8 mg/kg DOX. The enzymes contained SOD, catalase (CAT), glutathione peroxidase (GSH-Px) and glutathione reductase (GR) [35]. Lactate dehydrogenase (LDH) and α-hydroxybutyrate dehydrogenase (α-HBDH) in cardiomyocytes were marks to evaluate the tissue injuries.…”
Section: Radical Scavenger: Prevent Oxidative Damage From Dox and Ccl4mentioning
confidence: 99%